Anterior thalamic nuclei deep brain stimulation inhibits mossy fiber sprouting via 3′,5′-cyclic adenosine monophosphate/protein kinase A signaling pathway in a chronic epileptic monkey model - Ting-Ting Du; Ying-Chuan Chen; Guan-Yu Zhu; De-Feng Liu; Yu-Ye Liu; Tian-Shuo Yuan; Xin Zhang; Jian-Guo Zhang; Ning-Ning Wang. (Chinese Medical Journal, 2021)
Abstract. Background. Anterior thalamic nuclei (ATN) deep brain stimulation (DBS) is an effective method of controlling epilepsy, especially temporal lobe epilepsy. Mossy fiber sprouting (MFS) plays an indispensable role in the pathogenesis and progression of epilepsy, but the effect of ATN-DBS on MFS in the chronic stage of epilepsy and the potential underlying mechanisms are unknown. This study aimed to investigate the effect of ATN-DBS on MFS, as well as potential signaling pathways by a kainic acid (KA)-induced epileptic model. Methods. Twenty-four rhesus monkeys were randomly assigned to control, epilepsy (EP), EP-sham-DBS, and EP-DBS groups. KA was injected to establish the chronic epileptic model. The left ATN was implanted with a DBS lead and stimulated for 8 weeks. Enzyme-linked immunosorbent assay, Western blotting, and immunofluorescence staining were used to evaluate MFS and levels of potential molecular mediators in the hippocampus. One-way analysis of variance, followed by the Tukey post hoc correction, was used to analyze the statistical significance of differences among multiple groups. Results. ATN-DBS is found to significantly reduce seizure frequency in the chronic stage of epilepsy. The number of ectopic granule cells was reduced in monkeys that received ATN stimulation (P < 0.0001). Levels of 3′,5′-cyclic adenosine monophosphate (cAMP) and protein kinase A (PKA) in the hippocampus, together with Akt phosphorylation, were noticeably reduced in monkeys that received ATN stimulation (P = 0.0030 and P = 0.0001, respectively). ATN-DBS also significantly reduced MFS scores in the hippocampal dentate gyrus and CA3 sub-regions (all P < 0.0001). Conclusion. ATN-DBS is shown to down-regulate the cAMP/PKA signaling pathway and Akt phosphorylation and to reduce the number of ectopic granule cells, which may be associated with the reduced MFS in chronic epilepsy. The study provides further insights into the mechanism by which ATN-DBS reduces epileptic seizures.